Experimental and theoretical evidence of P-type conduction in fluorinated hexagonal boron nitride nano-sheets. Issue 6 (15th April 2020) - Ahmad, Aqrab ul; Liang, Hongwei; Ali, Sajid; Dastgeer, Ghulam; Abbas, Qasim; Farid, Amjad; Abbas, Akmal; Idrees, Asim; Iqbal, Muzammil; Farooq, Zahid
Abstract: The structural and electronic transport properties of Fluorine-doped boron nitride nanosheets (F-BNNSs) were investigated in a back-gate assisted field-effect transistor (FET) to exhibit the recognition of excellent p-type conduction because of Fluorine-doping. It was observed that the drain current was modulated by gating and increased significantly with the applied negative gate voltage, suggesting the predomination of holes. Moreover, theoretical calculations predicts, the formation of acceptor states at the fermi-level, supporting experimental results that fluorinated h-BN acts as a P-type semiconductor. Parameter together, with the ON/OFF ratio, resistivity and holes concentration, was additionally retrieved from the Ids -Vds curves. Our results suggest that such type of novel device description is a valuable approach to disclose the particular properties of fluorine functionalized BNNSs.